Cost Estimation for Software Development Using Function Point Analysis Method - Lumba, Ester; Widyaningrum, Destriana; Waworuntu, Alexander (IJNMT (International Journal of New Media Technology), 2024)
Software development requires substantial financial resources. This study aims to examine the cost estimation for software development. The complexity of the software, its intangibility as a non-physical product, the technology utilized, and human resources can all influence the determination of software development costs. The method used for cost estimation is Function Point Analysis with a case study approach. The researchers conducted a case study on the software development for an employee savings and loan cooperative at XYZ Company. The result of this study is a cost recommendation that can serve as a reference for selecting software development vendors by the cooperative's management.